In Vitro Dissolution Profile of Dapagliflozin: Development, Method Validation, and Analysis of Commercial Tablets - Rafaela Zielinski Cavalheiro de Meira; Aline Biggi Maciel; Fabio Seigi Murakami; Paulo Renato de Oliveira; Larissa Sakis Bernardi (International Journal of Analytical Chemistry)
Dapagliflozin was the first of its class (inhibitors of sodium-glucose cotransporter) to be approved in Europe, USA, and Brazil. As the drug was recently approved, there is the need for research on analytical methods, including dissolution studies for the quality evaluation and assurance of tablets. The dissolution methodology was developed with apparatus II (paddle) in 900 mL of medium (simulated gastric fluid, pH 1.2), temperature set at 37±0.5°C, and stirring speed of 50 rpm. For the quantification, a spectrophotometric (λ=224 nm) method was developed and validated. In validation studies, the method proved to be specific and linear in the range from 0.5 to 15 μg·mL−1 (r2=0.998). The precision showed results with RSD values lower than 2%. The recovery of 80.72, 98.47, and 119.41% proved the accuracy of the method. Through a systematic approach by applying Factorial 23, the robustness of the method was confirmed (p>0.05). The studies of commercial tablets containing 5 or 10 mg demonstrated that they could be considered similar through f1, f2, and dissolution efficiency analyses. Also, the developed method can be used for the quality evaluation of dapagliflozin tablets and can be considered as a scientific basis for future official pharmacopoeial methods.